The Digital Transformation of Organizational Learning: A Case Study of China Telecom - Wenhao Yu; Xiaoyan Shu; Bo Chang; Jiaqi He (Adult Education Research Conference, 2024)
Digital transformation of organizational learning becomes a key strategy for the development of organizations. Therefore, the purpose of this study is to take China Telecom as a case to explore the digital transformation of organizational learning and to find out the actions that China Telecom has taken to achieve the digital transformation of organizational learning.
Keywords: Digital transformation; Organizational learning; Activity theory